Integrating Behavioral Economics into Islamic Education Management: Promoting Ethical Decision-Making in School Leadership - Ahmad Syadidunniam; Ahmad Royani; Nur Ittihadatul Ummah; Siti Aminah (Journal of Psychological Insight, 2026)
Ethical leadership in Islamic educational management often faces challenges stemming from behavioral biases that affect decision-making. This study aims to analyze how nudge-based leadership can enhance the ethical and moral quality of school principals’ decision-making within an Islamic educational context. Employing a qualitative case study design, data were collected from school leaders and senior teachers through in-depth interviews, participatory observation, and document analysis, and analyzed using interpretative and content analysis within a behavioral ethical framework. The findings reveal that leadership practices based on moral modeling, moral reminders, and Islamic choice architecture effectively mitigate social-affinity bias, status quo bias, and overconfidence bias in leadership decisions. These strategies foster ethical behavior by embedding values of amanah, adl, ikhlas, and ihsan into daily organizational routines rather than relying on coercive authority. The novelty of this study lies in integrating nudge theory from behavioral economics with Islamic educational management to offer a value-based behavioral leadership model. The study implies that ethical governance in Islamic schools can be strengthened through a non-coercive behavioral design that aligns spiritual values with managerial practices.